2022
DOI: 10.1088/2752-5295/ac7d68
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic aerosol impacts on Pacific Coast precipitation in CMIP6 models

Abstract: Studies show anthropogenic aerosols (AAs) can perturb regional precipitation, including the tropical rain belt and monsoons of the Northern Hemisphere (NH). In the NH mid-latitudes, however, the impact of AAs on regional climate and precipitation remains uncertain. This work investigates the influence of AAs on wintertime precipitation along the North American Pacific Coast using models from the Coupled Model Intercomparison Project phase 6 (CMIP6). Over the early to mid-20th century, when U.S. and European A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…C07 shows significant overestimation (271.84%), likely due to its complex terrain in this region, featuring mountains, ocean interactions with land, and persistent snow cover, presenting challenges in climate modeling (e.g., Allen & Zhao, 2022; Li et al., 2022; Masud et al., 2021; Zhang et al., 2022). These challenges are also common in the Yukon River catchment C11 (118.68% bias).…”
Section: Resultsmentioning
confidence: 99%
“…C07 shows significant overestimation (271.84%), likely due to its complex terrain in this region, featuring mountains, ocean interactions with land, and persistent snow cover, presenting challenges in climate modeling (e.g., Allen & Zhao, 2022; Li et al., 2022; Masud et al., 2021; Zhang et al., 2022). These challenges are also common in the Yukon River catchment C11 (118.68% bias).…”
Section: Resultsmentioning
confidence: 99%
“…While these trends were often attributed to internal variability, we show evidence with CESM2 that they are, in part, a forced response to anthropogenic aerosols (AA; up to 42% of the observed precipitation trend). Specifically, the AA‐driven negative PDV‐like pattern originates from the post‐1980 shift of aerosol emissions from the Western to the Eastern Hemisphere, which has been suggested to be conducive to SWUS precipitation declines (Allen & Zhao, 2022; Allen et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are two modes to describe the historical AA emissions (Kang et al., 2021; Shi et al., 2022, 2023): (a) the aerosol increase mode, a global aerosol increase in the mid‐20th century, inducing Northern Hemisphere cooling, and (b) the aerosol shift mode, an aerosol emission shift from the Western to the Eastern Hemisphere since 1980, inducing a negative PDV‐like SST pattern. Idealized experiments with prescribed strong radiative forcings from aerosols (e.g., 5–10 times the observed emissions; Allen et al., 2020; Dow et al., 2021) and transient historical aerosols forcing (Allen & Zhao, 2022) show that AA, especially black carbon emissions from Asia, can induce a negative PDV‐like pattern, weaken the AL, and influence precipitation over Western North America. Given the anticipated regional changes to aerosol emissions in the near future (Persad et al., 2022), understanding its influence on historical precipitation trends is key to develop more robust future projections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have found a connection between the NAO and the AMOC [48][49][50] , with a positive NAO leading to a stronger AMOC by extracting heat from the subpolar gyre. Similarly, several studies have found that anthropogenic aerosols, through heterogeneous heating/cooling and the generation of Rossby waves [51][52][53][54] , can trigger atmospheric teleconnection (e.g., remote SLP perturbations). Although we do not pursue this farther here, we note the bulk of the 1960-1990 BMB anthropogenic aerosol burden increase occurs over Canada (Fig.…”
Section: Additional Bmb Responsesmentioning
confidence: 95%